Significado de las pautas comunicacionales entre padres e hijos de los grados de tercero a quinto de primaria de la institución educativa San Rafael que faciliten un proceso de mediación familiar - Ramírez Peña, Yunis Paola (Universidad Antonio Nariño, 2023)
The general objective of the present work is to determine the meaning of the communication guidelines between parents and children from the third to fifth grades of primary school of the San Rafael educational institution that facilitate a family mediation process, in the city of Sincelejo. The type of research is qualitative, the methodological design approach is hermeneutic phenomenological, with a descriptive scope. It was possible to determine family guidelines oriented to conflictive, distant relationships, problems with the hierarchy, diffuse limits, coalitions, difficulties between parents and children, at the same time efficient parental alliances and actions were evidenced, distortions such as disconfirmation, rejection, rigid complementarity were identified